2016
DOI: 10.1016/j.tim.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

RNA Structure Duplications and Flavivirus Host Adaptation

Abstract: Flaviviruses include a highly diverse group of arboviruses with a global distribution and a high human disease burden. Most flaviviruses cycle between insects and vertebrate hosts; thus, they are obligated to use different cellular machineries for their replication and mount different mechanisms to evade specific antiviral responses. In addition to coding for viral proteins, the viral genome contains signals in RNA structures that govern the amplification of viral components and participate in triggering or ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
203
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(213 citation statements)
references
References 71 publications
8
203
0
Order By: Relevance
“…Flavivirus polymerase specifically recognizes the viral 5= UTR during viral RNA replication (24,25). In particular, SLA within the 5= UTR is predicted to form a "Y"-shaped secondary structure and serves as a promoter for NS5 polymerase binding and activity (25,27). Specific binding between NS5 and SLA was observed when SLA (70 nucleotides [nt]) had an additional ssRNA region at the 3= end ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Flavivirus polymerase specifically recognizes the viral 5= UTR during viral RNA replication (24,25). In particular, SLA within the 5= UTR is predicted to form a "Y"-shaped secondary structure and serves as a promoter for NS5 polymerase binding and activity (25,27). Specific binding between NS5 and SLA was observed when SLA (70 nucleotides [nt]) had an additional ssRNA region at the 3= end ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Specific binding between NS5 and SLA was observed when SLA (70 nucleotides [nt]) had an additional ssRNA region at the 3= end ( Fig. 1) (25,27). We thus constructed SLA with an additional 10 nt, containing the first 80 nt of the dengue virus genome, referred to here as SLA 80 , to study the interaction between SLA and NS5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…sfRNA production is conserved for all MBFs and TBFs, and although recent RNA structure analysis of ISF 3= UTRs failed to identify XRN1-resistant structures (33,34), it was previously reported that ISFs and NKVFs have conserved SL structures with putative pseudoknot structures in their 3= UTRs (35). Indeed, sfRNA production has been experimentally shown for several NKVFs and the ISF cell-fusing agent virus (36).…”
mentioning
confidence: 99%
“…485,486 The Gamarnik laboratory demonstrated that the evolutionary pressure on xrRNA2 sequences from DENV2 is different in mammalian and mosquito cells. 487 In mosquitos mutations that disrupt Xrn1 resistance appear, resulting in shorter sfRNA species, sfRNA2, sfRNA3, and sfRNA4 (see Figure 1), while in human cells sfRNA1 is the predominant product. 113 Mosquito-adapted DENV2 that produced shorter sfRNAs had a fitness disadvantage and triggered an increased immune response (IFN β and ISG15 gene expression) in human cells, but the same virus did not have an altered replication rate when grown in mosquito cells.…”
Section: Viral Countermeasures To Antiviral Host Factorsmentioning
confidence: 99%